Analysis of the Relationship Between Corporate Social Responsibility and Good Corporate Governance on Fee Audit and Firm Value - Retno Cahyaningati; Muhammad Miqdad; Alwan Sri Kustono (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose : This study aims to determine whether Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) affect audit costs and firm value, and to analyze the mediation relationship between audit costs and firm value. Design/methodology/approach : Data collection through this case is on companies in Indonesia that are listed on the Corporate Governance Perception Index (CGPI) between 2016 and 2018 with 33 firmyears observations. Findings: The results of the path analysis show that CSR has no effect on audit costs, CSR programs carried out and disclosed by the company are not included in the client's business audit by the auditor. The size of the CSR disclosure cannot affect the audit fee. Even though GCG has a positive effect on audit fees, companies with high CGPI scores can pay more audit fees because they have higher financial standards, so they choose the Big four KAP that are more integrated and have quality. Meanwhile, CSR and audit fees do not affect firm value. However, GCG has a significant negative effect on firm value. The analysis of the effect of mediation shows that audit fees cannot mediate between CSR and GCG on firm value. Research limitations/implications: Overall, the audit fee cannot reflect the company's risk which is taken into consideration in making investment decisions. This happens because in investment decisions, investors look more at short-term profits such as daily stock prices and profitability. Practical implications : This research can provide important implications for management and regulators, namely as an alternative in making investment decisions that can increase firm value. Paper type: This research is a development research that tries to analyze the indirect effect, so that researchers have a little difficulty determining the theories used to link the interplay of components that influence each other, so researchers must make an opinion to strengthen this research.